Information security theory and practice : 10th IFIP WG 11.2 International Conference, WISTP 2016, Heraklion, Crete, Greece, September 26?27, 2016, Proceedings /: 10th IFIP WG 11.2 International Conference, WISTP 2016, Heraklion, Crete, Greece, September 26?27, 2016, Proceedings. (2016) - Unknown
No abstract available